Kajian Karakteristik Fisik Tanah di Lahan Perkebunan Kelapa Sawit (Elaies guinensis Jacq.) Kebun Adolina PTPN IV pada Beberapa Generasi Tanam - Juliana Epesus Simarmata; Abdul Rauf; Benny Hidayat (Institut Pertanian Bogor, 2017)
Soil management on some plantation land uses, such as fertilizing, clearing, the use of heavy equipment will affect, and the soil properties of the land use. This study aims to determine changes in physical properties of soil in the plantation oil palm plantations Adolina PTPN IV on 3 generations of planting. It was conducted at Adolina Estate of PTPN IV, Serdang Bedagai, Sumatera Utara in July-December 2016. The method used in this research is survey method with descriptive analysis. Soil samples taken are controls are the land has never planted oil palm (K0), palm oil 1st generation (G1), 3rd generation (G3), and 4th generation (G4). The results showed that planting of oil palm in the Adolina Garden increased soil pore space, soil structure, increased humidity (temperature), soil texture, the ability of roots to penetrate the soil (solum), and increased organic material. But it does not give a noticeable change to the parameters of soil density, permeability, and carbon storage in the soil.